Engaging young people as partners for change: The UR Community project - Anthony Charles (International Journal of Children's Rights, 2019)
Despite young people's right to participate in decision making being enshrined in the UNCRC, it is not the case that they are universally able to be heard when adults make decisions concerning policy and service delivery. In fact, despite wishing to engage with adults decision makers, young people largely remain unable to do so. This article reports what happened when an innovative project, undertaken in partnership with young people was operationalised in Swansea. Through the project, UR Community, insights into how research can be better undertaken with young people and participation rights be realised at a local level are offered. Such insights are important, not least because they challenge what both young people and adults understand by participation, its power and exercise.